The Jewish Kulturbund Theatre Company in Nazi Berlin, Rebecca Rovit (Iowa City: University of Iowa Press, 2012), xii + 304 pp., illus., paperback 41.00 - Jelavich, Peter (Holocaust and genocide studies, 2014)
Rebecca Rovit has added an important volume to the slowly growing scholarly literature about the Kulturbund, established by the Nazis in 1933 to exclude and segregate German Jews into an increasingly constrained cultural sphere. In its time as well as today, the organization was controversial—accused, at worst, of collaboration with the Nazis—and Rovit does not shy away from laying out the accusations; at the same time, however, she shows great sympathy for the dilemmas confronting the people involved. Since hers is the first extended study of the theater and performance division of the Kulturbund, it brings to light a wealth of new information., Rovit concentrates on two dynamics: first, the “careful two-step dance” (p.